Literacy-related differences in morphological knowledge: A nonce-word study - Dąbrowska, Ewa; Pascual, Esther; Macías-Gómez-Estern, Beatriz; Llompart, Miquel (Frontiers in Psychology, 2023)
Using a nonce word inflection task, we examine the morphosyntactic productivity of adult native speakers of Spanish who are either beginning to learn to read and write (semi-literates) or have acquired literacy in late adulthood (late literates), as well as age-matched controls (high literates). High literates consistently provided the appropriate form more often than late-literates, who in turn were better than semi-literate participants. Crucially, group interacted with person, number, and conjugation, such that the between-group differences were larger for the less frequent cells in the paradigm, indicating that literacy-related differences are not merely a consequence of the high-literacy group being more engaged or test-wise. This suggests that the availability of written representations may facilitate the acquisition of certain aspects of grammar. We also observed vast individual differences in productivity with inflectional endings. These results add to the growing body of research which challenges the assumption that all native speakers converge on the same grammar early in development.